Strength deterioration mechanism of horizontal stratified cemented tailings backfill under uniaxial compression - Shuaijun Chen; Aibing Jin; Yiqing Zhao; Zhongshu Wang; Youmei Zheng (Case Studies in Construction Materials)
Horizontal stratified cemented tailings backfill (SCTB) inevitably appears in the underground stope. Exploring the mechanical characteristics of horizontal SCTBs and explaining the strength deterioration mechanism of horizontal SCTBs is essential for the strength design of backfill. In this study, experiments were used to investigate, on a macro-scale, the mechanical characteristics of horizontal SCTBs with varying filling interval time. Numerical simulations were utilized to explore the primary elements determining the strength of horizontal SCTBs from the micro-scale. The results show that, at the macro-scale, the interval time has an impact on the samples’ mechanical properties by affecting the stratified surface’s initial width. The change in the stratified surface’s initial width leads to a change in the stratified surface’s stiffness, which affects the mechanical properties of the sample. At the micro-scale, neither the stratified surface’s bonding strength nor its friction coefficient significantly affects the mechanical properties of horizontal SCTBs. The monti-form bulges with different heights reduce the stratified surface’s stiffness. Axial stress causes microcracks to form easily close to the stratified surface, destroying the sample’s integrity and reducing SCTB’s strength. The stiffness and number of stratified surfaces are the key variables impacting the mechanical properties of the horizontal SCTBs.